Large Igneous Province Sulfur Emissions Have Long‐Term (>1000 Years) Effects on the Ocean Carbon Cycle - Hee Jun Cheong; Tushar Mittal; Courtney Jean Sprain; Isabel M. Fendley (Geochemistry, Geophysics, Geosystems)
Abstract Large Igneous Province (LIP) eruptions are thought to have driven environmental and climate change over wide temporal scales ranging from a few to thousands of years. Since the radiative effects and atmospheric lifetime of carbon dioxide (CO2, warming) and sulfur dioxide (SO2, cooling) are very different, the conventional assumption has been to analyze the effects of CO2 and SO2 emissions separately and add them together afterward. In this study, we test this assumption by analyzing the joint effect of CO2 and SO2 on the marine carbonate cycle using a biogeochemical carbon cycle box model (Long‐term Ocean‐atmosphere‐Sediment CArbon cycle Reservoir Model). By performing model runs with very fine temporal resolution (∼0.1‐year timestep), we analyze the effects of LIP carbon and sulfur gas emissions on timescales ranging from an individual eruption (hundreds to thousands of years) to the entire long‐term carbon cycle (>100,000 years). We find that, contrary to previous work, sulfur emissions have significant long‐term (>1,000 years) effects on the marine carbon cycle (dissolved inorganic carbon, pH, alkalinity, and carbonate compensation depth). This is due to two processes: the strongly temperature‐dependent equilibrium coefficients for marine carbonate chemistry and the few thousand‐year timescale for ocean overturning circulation. Thus, the effects of volcanic sulfur are not simply additive to the impact of carbon emissions. We develop a causal mechanistic framework to visualize the feedbacks associated with combined carbon and sulfur emissions and the associated timescales. Our results provide a new perspective for understanding the complex feedback mechanisms controlling the environmental effects of large volcanic eruptions over Earth history.